Nutritional condition and IGF-1 and IGFBP-2 serum concentrations in students aged 7 to 9 attending two educational institutions (2016)
Introduction: Nutritional vulnerability is more evident during childhood, since malnutrition has an impact on academic performance and is linked to different diseases during this period. Likewise, an increase in the incidence and prevalence of obesity in children has been observed, therefore, researches that assess nutritional conditions of children attending schools may have high-impact results in terms of public health.Objective: To relate children’s nutritional condition by using anthropometry, with serum concentrations of insulin-like growth factor 1 (IGF-1) and its binding protein 2 (IGFBP-2).Materials and methods: A cross-sectional observational and comparative study was performed in children aged 7 to 9 attending two schools, one from the public sector and the other from the private sector. An anthropometric assessment was performed in 157 children, while IGF-1 and IGFBP (enzyme immunoassay) serum concentrations were measured in 81 children. Pearson’s coefficient, analysis of variance (ANOVA), Dunnet’s test and Games Howell’s test, with a 95% confidence interval and a p0.05 statistical significance, were considered for performing the statistical analysis.Results: Overweight and obesity were found in 46 subjects; the prevalence of obesity was higher in boys, while overweight prevalence was higher in girls. A direct relation between IGF-1 and height (p0,05) was observed, while an inverse relation between IGFBP-2 and BMI (p0,001) was found.Conclusions: IGF-1 serum concentrations were higher in students attending the public school.